PENGARUH ONLINE SHOPPING BESERTA PROGRAM POTONGAN HARGA DALAM ONLIE SHOP TERHADAP PERILAKU KONSUMEN - Ai Nining Yunita; Ghina Faadhilah; Nurjanah Dea Saputra (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine how much influence online shopping and discount programs have on the behavior of consumers who have accessed e-commerce. The data analysis technique used in this research is causal quantitative with descriptive statistical analysis method. Research subjects determined in this study are consumers who have accessed online shopping. The number of samples is 10 respondents. The independent variables in this study are online shopping, discounted prices consisting of quantity discounts, discounts and cash discounts, while the seasonal variable depends on consumer behavior. The study's findings revealed that the use of discounts can influence the behavior of online purchasing customers. Consumers are drawn to discounts when they are available. Discounts are enticing in and of themselves. At the same time, incentives entice customers to shop there for apparel. Consumer behavior is positively influenced by the quantity of clothes purchases for low price indicators and discount variables, as well as clothing purchase indicators.